1995
DOI: 10.1073/pnas.92.26.12485
|View full text |Cite
|
Sign up to set email alerts
|

Peptide synthesis using unprotected peptides through orthogonal coupling methods.

Abstract: We describe an approach to the synthesis of peptides from segments bearing no protecting groups through an orthogonal coupling method to capture the acyl segment as a thioester that then undergoes an intramolecular acyl transfer to the amine component with formation of a peptide bond. Two orthogonal coupling methods to give the covalent ester intermediate were achieved by either a thiol-thioester exchange mediated by a trialkylphosphine and an alkylthiol or a thioesterification by C"-thiocarboxylic acid reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
189
0
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(193 citation statements)
references
References 28 publications
0
189
0
2
Order By: Relevance
“…However, the development of native chemical ligation (NCL) methods using C-terminal peptide-thioesters (obtained from SPPS) that can be coupled without sidechain protection has provided strategies for the synthesis of larger peptides (>100 residues). 53,54 Recently, Torbeev and Kent reported the convergent chemical synthesis of a 203 residue ''covalent dimer'' of HIV-1 protease enzyme using NCL methods. The resulting enzyme molecule showed full catalytic activity and a high resolution crystal structure was reported.…”
Section: )''mentioning
confidence: 99%
“…However, the development of native chemical ligation (NCL) methods using C-terminal peptide-thioesters (obtained from SPPS) that can be coupled without sidechain protection has provided strategies for the synthesis of larger peptides (>100 residues). 53,54 Recently, Torbeev and Kent reported the convergent chemical synthesis of a 203 residue ''covalent dimer'' of HIV-1 protease enzyme using NCL methods. The resulting enzyme molecule showed full catalytic activity and a high resolution crystal structure was reported.…”
Section: )''mentioning
confidence: 99%
“…[1,35] Two variants of this approach were presented by Tam et al. [36] Both methods are also based on the sequential capture and intramolecular acyl transfer principle where a thioacid is alkylated to form an intermediate thioester that will rearrange to give the cysteine at the ligation site ( Figure 6C). Raines et al have showed that the concept of NCL can also be extended to include selenocysteines.…”
Section: Thioacid and Thioester Mediated Ligationsmentioning
confidence: 99%
“…Though DNA-based site-directed mutagenesis is a powerful tool for protein design and engineering, the search for innovative approaches for construction of proteins has continued (Schnolzer & Kent, 1992;Chang et al, 1994;Jackson et al, 1994;Tam et al, 1995). This is in consonance with the protein chemists' desire to expand the range of modification of the covalent structure of proteins, including incorporation of noncoded/nonstandard amino acids or other designer "fixed elements of 3D structure" (Balaram, 1992;Schnolzer & Kent, 1992), since only limited variation is possible through genetic approaches due to inherent problems of the ribosomal protein synthesizing machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, failure of semisynthesis of S-peptide may be a consequence of high flexibility around the 9-10 peptide bond due to its proximity to the helix stop signal. The results suggest that protease-mediated ligations may be achieved by design and manipulation of the conformational aspects of the product.Keywords: conformation; organic cosolvent; proteosynthesis; reverse proteolysis; semisynthesis Recent years have seen remarkable progress in the area of synthetic protein chemistry toward developing strategies for chemical ligation of polypeptide fragments for construction of natural as well as novel proteins based on de novo design principles (Dawson & Kent, 1993;Dawson et al, 1994;Gaertner et al, 1994;Jackson et al, 1994;Liu & Tam, 1994;Tam et al, 1995;Wallace, 1995). The protease-catalyzed ligation of protein/peptide fragments offers the same flexibility to a selected segment as that available in modular chemical ligation strategy and may act as a bridge between chemical and genetic approaches for construction of pro--Reprint requests to: Rajendra P. Roy, National…”
mentioning
confidence: 99%